Exploring Transdisciplinarity in Art and Sciences (Springer International Publishing, 2018)
Chapter "Composing Music from Neuronal Activity: The Spikiss Project" is available open access under a Creative Commons Attribution-NonCommercial 4.0 International License via link.springer.com.